Central Asia-West Asia-South Asia Connectivity Building an Upgraded Version of the CPEC - Chen, Ruihua (Pacific International Journal, 2023)
The world is undergoing profound changes unprecedented in a century, jointly building the Belt and Road is an important guarantee for maintaining global stability and development in response to profound changes, and building a new development pattern with the domestic cycle as the main body and the domestic and international dual cycles promoting each other is a strategic choice to respond to the changes in the complex situations. With the in-depth advancement of the BRI, Xinjiang has actively served and integrated into the new development pattern, becoming a hub node to build a domestic and international dual cycle facing Eurasia. As the flagship project of the BRI and the landmark project of the rise of land power in the post-global era, the CPEC is of great strategic significance in responding to profound changes and building a new development pattern. With the stability of Central Asia, West Asia, and South Asia, we have taken the initiative to accelerate regional connectivity and it is both necessary and feasible to build an upgraded version of the CPEC.